La calidad del servicio educativo y de atención de los Centros infantiles del Buen Vivir, Perspectivas y Expectativas de los padres de familia :estudio de caso en el Cibv “Ernesto Noboa y Caamaño” de la comunidad de Pesillo, Parroquia Olmedo, Cantón Cayambe, Provincia de Pichincha - Colcha Alba, Elsa Margoth (2014)
This research work was conducted at the CIBV "Ernesto Noboa y Caamano" Pesillo community, parish Olmedo, Canton Cayambe; This was done with the participation of teachers, parents and mothers of the institution and the community. It was necessary to analyze the quality of education and infant care centers for Good Living from the perspectives and expectations of parents; taking into account that early childhood is considered the primary stage in human life, where the development of skills and abilities is power. For this we have taken into account the various theories of development proposed by several authors have presented their research, among the highlights are: Piaget, Vygotsky, Ausubel, Dewey, Montessori. Based on these investigations the development of early childhood also addressed from the cultural, spiritual and ancestral rescuing community values.